A trial of drug‐induced sleep endoscopy in the surgical management of sleep‐disordered breathing1. (5th September 2012) - Gillespie, M. Boyd; Reddy, Ryan P.; White, David R.; Discolo, Christopher M.; Overdyk, Frank J.; Nguyen, Shaun A.
Abstract Objectives/Hypothesis: To determine the reliability and validity of drug‐induced sleep endoscopy (DISE) for patients undergoing surgery for sleep‐disordered breathing (SDB). Study Design: Non‐randomized, prospective clinical trial. Methods: Patients with sleep‐disordered breathing were evaluated for multi‐level upper airway surgery by awake and drug‐induced sleep endoscopy to identify levels and degree of airway collapse. The reliability of a drug‐induced sleep endoscopy rating index was assessed by comparing scores of three blinded investigators. The validity was assessed by comparison of drug‐induced sleep endoscopy index scores from awake and drug‐induced sleep endoscopy; correlation between drug‐induced sleep endoscopy scores and Apnea‐Hypopnea Index; and determination whether drug‐induced sleep endoscopy affected the original surgical plan. Results: Thirty‐eight patients (22 M, 16 F) underwent preoperative assessment with awake and drug‐induced sleep endoscopy. Drug‐induced sleep endoscopy was successfully performed in all but one patient (97%) who became combative during propofol infusion. Using an internal airway grading scale, drug‐induced sleep endoscopy demonstrated more severity of collapse than awake endoscopy (P = 0.0001). The surgical plan was changed after drug‐induced sleep endoscopy in 23 (62%) cases and unchanged in 14 (38%). The majority (73%) had multi‐segmental airway collapse with fewer having single‐level palatal (16%) or tongue base (11%) collapse. Scoring of drug‐induced sleep endoscopy videos demonstrated good intrarater (κ 0.61) and interrater (κ 0.65) correlation. Conclusions: Drug‐induced sleep endoscopy provides more clinical information to assess airway function and collapse than awake endoscopy alone and assists in the surgical planning. Additional investigation is needed to standardize drug‐induced sleep endoscopy techniques, training, and interpretation. Laryngoscope, 2013